Market Mechanisms in the Qur’an: A Tafsir Analysis of Business Competition and the Role of Government in the Modern Marketplace Context - Indri Astuti; Muhammad Mukharom Ridho; Dafina Salsabila (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study aims to examine market mechanisms based on Qur’an, Surah An-Nisa verse 29, and their relevance to business competition practices in the marketplace era. It also highlights the role of the government in building a conducive business climate to achieve a healthy and equitable economy. The research method used is qualitative with a library research approach. Data were collected from various sources, including classical Qur’anic exegesis (tafsir), academic literature, books, and relevant research articles, and were then analyzed using content analysis techniques. The results show that Islam fundamentally allows market mechanisms to operate naturally without intervention from any party. Economic activities must be conducted in accordance with Sharia principles, based on mutual consent among the involved parties, and must avoid actions that harm others. However, the verse also implies the need for government intervention in certain circumstances when the market fails to function properly, such as in cases of monopoly practices or unfair competition in both traditional and digital markets. In the Indonesian context, the government has enacted Law Number 5 of 1999 as a legal instrument prohibiting monopolistic practices and unfair business competition. In addition to this regulation, the government carries out its role through supervisory and protective functions. Economic policy formulation is also undertaken to support business sustainability. Therefore, the government’s role is not only to maintain the stability of market mechanisms but also to ensure that the principles of justice and welfare are realized for all business actors.